Epidemiological Data of Postcricoid Cancers from a Tertiary Cancer Hospital: First Report from Northern Andhra Pradesh - Venkata Krishna Reddy Pilaka; K. G. K. Deepak; Sushmitha Chowdary; Kanhu Charan Patro; Partha Sarathi Bhattacharya; Murali Krishna Voonna (Indian Journal of Public Health)
Postcricoid (PC) cancer is a global rarity, however, the burden of disease in India is little known. The data of PC cancers from Northern Andhra Pradesh (AP) are scarce due to poor reporting. This is an epidemiological study of PC cancer from a tertiary cancer hospital in Northern AP. ArcGIS software is used for mapping the cases across three districts of Northern AP. The incidence of PC cancers reported at Mahatma Gandhi Cancer Hospital and Research Institute, Visakhapatnam (VSKP), was 3.5, 2.7, and 3.3 cases per one lakh population in the districts of VSKP, Srikakulam (SKLM), and Vizianagaram, respectively. The highest incidence (cases per one lakh population) of 11.2 was found to be in Anakapalli mandal of VSKP district followed by SKLM, Sabbavaram, Yelamanchili, and Vizianagaram mandals with 10, 8.9, 8.5, and 8 cases, respectively. This is the first reported epidemiological study of PC cancer from Northern AP.